Self-assessment concerning the quality of life among family nurses - Zuń, Katarzyna; Fidecki, Wiesław Marian; Wysokiński, Mariusz; Sienkiewicz, Zofia; Kulina, Dorota; Zych, Magdalena; Jędrzejewska, Aneta; Kijowska, Agnieszka (Journal of Education, Health and Sport, 2018)
Abstract Introduction. Due to the numerous responsibilities, perceived accountability and significant psychophysical workload, there is a decrease in self-assessment concerning the quality of life among nurses of various specializations. The level of quality of life depends on various factors, which impact is individually dependent according to one’s subjective perception.Aim. The aim of the research was to determine the self-assessment concerning the quality of life among family nurses.Materials and method. The group of respondents consisted of 152 professionally active family nurses. The quality of life was examined with a standardized tool: the WHOQOL-Bref scale.Results. The examined family nurses rated their quality of life at an average of 3.79±0.78, while the self-assessment regarding their health amounted to the average of 3.69±0.84. The highest marks were received by the social field (72.25±18.44) among respondents. They slightly lower rated the physical domain (69.59 ±14.46) as well as the environmental domain (66.46±13.08). Whereas, the lowest rating was assigned to the psychological domain (59.96±12.13).Conclusion. The self-assessment concerning the quality of life among family nurses is characterized as on an average level. The age of the respondents significantly differentiates the quality of life of the researched occupational group. Moreover, along with an increase in vocational education, the quality of life perception of the nurses’ increases.Key words: quality of life, family nurses